Lukas’ evangelium, fortolket af Niels Willert - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2024)
The article reviews Niels Willert’s commentary on the Gospel of Luke. On the one hand, the book presents a solid traditional analysis of the gospel. The interpretation lives up to international research. It is welcome in a Danish context and will be of benefit for many readers of the New Testament. On the other hand, it has a provocative profile and challenges accepted views. It promotes controversial ideas: It sees Luke-Acts as one single work in two volumes. It dates the Lukan writings extremely late, i.e. 120-140. It adheres to the Farrer-hypothesis concerning the synoptic problem. It takes the Gospel of John to be among Luke’s sources. These ideas are discussed critically in the review, and arguments are raised against the late dating and the relation to the Fourth Gospel. However, the conclusion is that these hypotheses do not affect the exegesis of the individual pericopes. Therefore, the commentary is warmly recommended for all serious readers of the Gospel of Luke.